Foreign Stakeholders' Perception Survey - Mir, Aized H.; Durrani, Amer Z.; Gilani, Ijaz; Malik, Ermeena (World Bank, Washington, DC, 2014)
The literature review and especially the country specific assessments and reports indicated that the capacity of a local construction industry may be limited due to a wide variety of reasons. Therefore, a survey of foreign stakeholders was planned as part of the Pakistan Infrastructure Implementation Capacity Assessment (PIICA). Its objective was to obtain insight on the perceptions of international contractors and consultants and their level of interest in pursuing business in Pakistan. The following were the key issues explored: (i) For countries with the worst business environment, what are the various issues that make the business environments in these countries challenging? Are such challenges acceptable? (ii) For countries with the best business environment, how are the same issues rated? (iii) What would attract foreign stakeholders to pursue business in Pakistan and what deters them? (iv) What are the general perceptions about the business environment in Pakistan? (v) If Pakistan is not on top of the list for exploring business, is it because there is plenty of work available elsewhere?